Chicken scratches : Grade A poultry poetry and rooster rhymes - Shannon, George (Chronicle Books, 2010)
Celebrates the eccentric behavior of chickens, from a chicken who laid an egg as she danced, to a chicken who dresses up on Halloween as a deviled egg, to a chicken who is a sumo wrestler.